THE EFFECTS OF SOCIAL MEDIA CONTENT CHARACTERISTICS ON CONSUMER ENGAGEMENT – A SYSTEMATIC LITERATURE REVIEW - Flavia HERLE (Annals of the University of Oradea: Economic Science)
This paper explores the relationship between social media content characteristics and consumer engagement. Utilising a systematic literature review, we analysed 89 relevant studies, highlighting key findings on how various content types, formats and other characteristics affect user engagement. Our findings reveal that while high-quality visual content generally enhances engagement, emotional appeal and interactivity are essential for fostering connections with consumers. However, we identified several gaps in the literature, which future research should address to clarify how social media content should be designed and delivered in order to maximise consumer engagement.